The stigma of the Chinese poll tax in colonial New Zealand. (February 2023) - Vosslamber, Rob; Yong, Sue
This article considers colonial New Zealand's poll tax on Chinese immigrants. Poll taxes were recognised as a badge of slavery and therefore could be used to discriminate and stigmatise. This could only happen if the Chinese had first been labelled, stereotyped and separated from 'normal' society, and deprived of their status as full human beings. Anti-Chinese attitudes amongst politicians, lobby groups, the media and society in general paved the way for discriminatory legislation which imposed the poll tax. Since the Chinese were regarded as less than fully human, their liability to discrimination in the form of a poll tax was considered to be justified. Applying Goffman's theory of stigma, as developed by Link and Phelan, this article analyses why the poll tax was discriminatory by referring to social discourse and to attitudes amongst the politicians and media. The poll tax illustrates how the practice of taxation contributed to discrimination and dehumanisation by referring to a specific form of taxation.